Desarrollo de un prototipo de una unidad de control de fluído hídrico para un proceso de mezclado en una empresa embutidora - Valenciano-Rojas, Mario Alberto (Instituto Tecnológico de Costa Rica, 2019)
The project will be published in the Technological Institute of Costa Rica, at the headquarters of San Carlos, in the first semester of 2019. In a combination with the company Cinta Azul Ltd., in San Antonio del Tejar located in Alajuela and which one was acquired by the multinational Cargill in 1999 where currently a large percentage of the sausages consumed in the country are produced. To produce sausages, the plant needs water as raw material, which must be transferred to a machine that is responsible for mixing it with other products to make a paste. In this process the water is carrying by a kind of "container" (see figure 1.1), which is filled manually and must be lifted until it gets empty. The current way of transporting the water generates inconveniences, mainly because it does not control in an efficient way the weight of the "container" filled with water and this generates waste of time, hydric resources and money. Affecting straight the operations of Cinta Azul plant. The project is focused on control the amount of hydric resource used to produce the paste necessary in the production of sausages by an electronic method which controls and manages the amount of water used. Also, this project allows the standardization of the dispensing water process to make the whole process more effectively than the techniques already used in the company. In addition, we seek to create a record of the weights into a database. This report shows the design process of the dosage control system and the registration of the amount of water applied in the process area through the electronic control system. The execution and the verification of its performance by simulations and tests in the cell FESTO present in the SIMTEC Laboratory at the Technological Institute of Costa Rica, at the headquarters of San Carlos.
Proyecto de Graduación (Licenciatura en Ingeniería en Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2019.
Keywords: Sistemas electrónicos; Recursos hídricos; Máquinas electrónicas; Bases de datos; Dosificación; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics